1989
DOI: 10.1113/jphysiol.1989.sp017445
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulation of left atrial receptors on coronary blood flow in anaesthetized dogs.

Abstract: SUMMARY1. To determine whether stimulation of atrial receptors reflexly affects coronary blood flow, experiments were performed in seven dogs anaesthetized with achloralose. The left upper and middle pulmonary vein-atrial junctions and atrial appendage were stretched by distension of small balloons. Coronary blood flow was measured using an electromagnetic flowmeter positioned around the origin of the left anterior descending or circumflex coronary artery.2. Following prevention of the reflex increase in heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Efferent cardiac nerves are believed to be involved in the reflex changes in coronary blood flow caused by stimulation of carotid sinus baroreceptors, atrial and ventricular receptors (e.g. Feigl, 1983;Ito & Feigl, 1985; Coleridge, Coleridge, Clozel, Hoffman, Roberts & Pisarri, 1987;Drinkhill, Kaye & Mary, 1989a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efferent cardiac nerves are believed to be involved in the reflex changes in coronary blood flow caused by stimulation of carotid sinus baroreceptors, atrial and ventricular receptors (e.g. Feigl, 1983;Ito & Feigl, 1985; Coleridge, Coleridge, Clozel, Hoffman, Roberts & Pisarri, 1987;Drinkhill, Kaye & Mary, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…Distal to the probe, a plastic snare was placed around the artery for the assessment of zero flow. The flow probe was calibrated in situ as previously described (Drinkhill et al 1989a). To pace the heart, electrodes were placed on the left atrial appendage and connected to a stimulator (WPI Digipulser W-P Instruments Inc., New Haven, CO, USA) which delivered pulses of 3-5 V, 2 ms duration at the required frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In each experiment recordings are shown of, from above down, mean femoral arterial blood pressure (FAP), mean blood pressure in a small branch of the left anterior descending coronary artery (CAP), mean and phasic coronary blood flow (CBF), mean left atrial pressure (LAP) and the electrocardiogram (ECG). Reproduced from Drinkhill, Kaye & Mary, 1989a. the carotid region and which affect the left ventricular inotropic state (see Mary, 1987). Stimulation of the atrial receptors also causes reflex decreases in plasma renin activity and vasopressin level (Bennett, Linden & Mary, 1984;Drinkhill, Hicks, Mary & Pearson, 1988).…”
Section: A Trial Receptorsmentioning
confidence: 99%
“…Because of this uncertainty, this review will concentrate on the effect of stimulation of the atrial receptors which discharge into afferent myelinated vagal nerves. In a recent study, stimulation of left atrial receptors in anaesthetized dogs was shown to cause a reflex increase in heart rate which was associated with an increase in mean coronary blood flow (Drinkhill, Kaye & Mary, 1989a). When the reflex tachycardia was prevented by atrial pacing or ,-adrenergic blockade by propranolol, this same stimulation caused a decrease in mean coronary blood flow (Fig.…”
Section: A Trial Receptorsmentioning
confidence: 99%
See 1 more Smart Citation